If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(n + 2) = 2 + -3(n + -8) Reorder the terms: 5(2 + n) = 2 + -3(n + -8) (2 * 5 + n * 5) = 2 + -3(n + -8) (10 + 5n) = 2 + -3(n + -8) Reorder the terms: 10 + 5n = 2 + -3(-8 + n) 10 + 5n = 2 + (-8 * -3 + n * -3) 10 + 5n = 2 + (24 + -3n) Combine like terms: 2 + 24 = 26 10 + 5n = 26 + -3n Solving 10 + 5n = 26 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 10 + 5n + 3n = 26 + -3n + 3n Combine like terms: 5n + 3n = 8n 10 + 8n = 26 + -3n + 3n Combine like terms: -3n + 3n = 0 10 + 8n = 26 + 0 10 + 8n = 26 Add '-10' to each side of the equation. 10 + -10 + 8n = 26 + -10 Combine like terms: 10 + -10 = 0 0 + 8n = 26 + -10 8n = 26 + -10 Combine like terms: 26 + -10 = 16 8n = 16 Divide each side by '8'. n = 2 Simplifying n = 2
| -1-2x=9 | | 9x^2+7x+8=0 | | x+394=6690 | | 90=-4+2(5-6v) | | 5x-8=-x-4 | | 3=5=x/2 | | f(x)=9x^2+7x+8 | | a^2+a-1+-a-1= | | 2x+22=60 | | 5k^2=5k | | 290688=bc | | -5(5n+4)=-145 | | -6H+3=9 | | 7x+12y=10 | | x=4-2(13) | | 5.6=4.7x-9 | | 7z+1=8z | | 1=2x^2-4x | | -12(x+1)+4(4x-3)=3(x-3)+14 | | 2w/2 | | 10/7h=170 | | 1/3(8x-16)=12 | | 6(x-9)=66 | | 4k^2-6=k^2+17k | | -120=y-47 | | 3(X+5)+3X=8X-X(2)+15.75-13.15 | | -x-2(-x-3)=-4+x | | 0=2x(2)-4x | | 6(4-2y)-1y=-145 | | z-53=798 | | 3x^2+9x-5x+4x^2= | | 501169=bxc |